High Frequency Regeneration of Plantlets from Immature Male Floral Explants of Musa paradisica cv. Puttabale - AB Genome - Kumar, K. Girish; Krishna, V.; Venkatesh, Venkatesh; Pradeep, K. (Plant Tissue Culture and Biotechnology, 2011)
High frequency in vitro regeneration for mass multiplication from immature male floral explants of Musa paradisica cv. Puttabale on MS supplemented with adenine sulfate (160 mg/l), tyrosine (100 mg/l), sucrose (40 g/l) and gelled with 0.8 g/l agar was attempted. For callus induction the combinations of 2, 4-D and BAP were tested at 1.0 - 10.0 mg/l and 0.5 - 5.0 mg/l, respectively. For shoot bud formation combinations of BAP and TDZ were also tested at 1.0 - 5.0 mg/l and 0.1 - 0.5 mg/l, respectively. Luxuriant proliferation and high frequency induction (97.0%) of callus was noticed from the accessory floral part of the explant at 7.0 mg/l 2, 4-D and 1.0 mg/l BAP, later it preceded towards the gynoecium. Interaction of BAP (2.0 5.0 mg/l) and TDZ (0.2 - 0.5 mg/l) would provoke high frequency shoot bud differentiation from the floral calli and a mean of 29.40 ± 6.10 shootlets per callus was obtained at 4 mg/l BAP and 0.4 mg/l TDZ. Rooting of the microshoots was achieved on MS containing 0.6 mg/l NAA and 0.2% activated charcoal. Key words: Musa pardisica, Puttabale, Regeneration, Male floral explants. D. O. I. 10.3329/ptcb.v21i2.10243 Plant Tissue Cult. & Biotech. 21(2): 199-205, 2011 (December)